2018
DOI: 10.1016/j.copbio.2018.01.025
|View full text |Cite
|
Sign up to set email alerts
|

A guide to manufacturing CAR T cell therapies

Abstract: In recent years, chimeric antigen receptor (CAR) modified T cells have been used as a treatment for haematological malignancies in several phase I and II trials and with Kymriah of Novartis and Yescarta of KITE Pharma, the first CAR T cell therapy products have been approved. Promising clinical outcomes have yet been tempered by the fact that many therapies may be prohibitively expensive to manufacture. The process is not yet defined, far from being standardised and often requires extensive manual handling ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
264
0
9

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 302 publications
(276 citation statements)
references
References 87 publications
(83 reference statements)
3
264
0
9
Order By: Relevance
“…Furthermore, we have found that this manufacturing change can also increase the potency of the resulting CAR T cell product 40 . Guidelines for the development of commercial CAR cell products have been developed and are likely to evolve as our knowledge and experience grow 41,42 .…”
Section: Wwwnaturecom/nrclinoncmentioning
confidence: 99%
“…Furthermore, we have found that this manufacturing change can also increase the potency of the resulting CAR T cell product 40 . Guidelines for the development of commercial CAR cell products have been developed and are likely to evolve as our knowledge and experience grow 41,42 .…”
Section: Wwwnaturecom/nrclinoncmentioning
confidence: 99%
“…This issue is compounded by the observation that many academic and commercial vector manufacturing facilities were designed with scales necessary to support ex-vivo programs in mind [102]. Furthermore, wait times to access such manufacturing facilities appear to be increasing [103]—in part due to spectacular successes achieved with immuno-oncology ex-vivo gene/cell therapy approaches such as chimeric antigen receptor T-cell based therapies [104]. To facilitate the translational success emerging with in-vivo gene transfer, considerable focus must be brought to bear on the cost-of-goods associated with manufacturing vectors.…”
Section: Expert Opinionmentioning
confidence: 99%
“…Nevertheless, the production of primary T-cells has often been considered optimal under static conditions despite the cells being a suspension cell type by nature, with many clinical and small-scale processes opting to employ static T-flask or sterile culture bags for cell production (Vormittag, Gunn, Ghorashian, & Veraitch, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…To overcome these challenges, clinical research and commercial groups have used the use of rocking motion bioreactor systems (e.g., GE Healthcare's WAVE bioreactor or BIOSTAT RM from Sartorius Stedim Biotech), which improve the homogeneity of the culture, sampling and implementation of process control strategies (Marsh et al, 2017;Vormittag et al, 2018). To overcome these challenges, clinical research and commercial groups have used the use of rocking motion bioreactor systems (e.g., GE Healthcare's WAVE bioreactor or BIOSTAT RM from Sartorius Stedim Biotech), which improve the homogeneity of the culture, sampling and implementation of process control strategies (Marsh et al, 2017;Vormittag et al, 2018).…”
Section: Introductionmentioning
confidence: 99%